Activation of endogenous FAK via expression of its amino terminal domain in Xenopus embryos. - Nicoletta I Petridou; Panayiota Stylianou; Neophytos Christodoulou; Daniel Rhoads; Jun-Lin Guan; Paris A Skourides (PLoS ONE, 2012)
BACKGROUND: The Focal Adhesion Kinase is a well studied tyrosine kinase involved in a wide number of cellular processes including cell adhesion and migration. It has also been shown to play important roles during embryonic development and targeted disruption of the FAK gene in mice results in embryonic lethality by day 8.5. PRINCIPAL FINDINGS: Here we examined the pattern of phosphorylation of FAK during Xenopus development and found that FAK is phosphorylated on all major tyrosine residues examined from early blastula stages well before any morphogenetic movements take place. We go on to show that FRNK fails to act as a dominant negative in the context of the early embryo and that the FERM domain has a major role in determining FAK's localization at the plasma membrane. Finally, we show that autonomous expression of the FERM domain leads to the activation of endogenous FAK in a tyrosine 397 dependent fashion. CONCLUSIONS: Overall, our data suggest an important role for the FERM domain in the activation of FAK and indicate that integrin signalling plays a limited role in the in vivo activation of FAK at least during the early stages of development.